2023
DOI: 10.1002/dmrr.3672
|View full text |Cite
|
Sign up to set email alerts
|

High‐normal unconjugated bilirubin is associated with decreased risk of chronic kidney disease in type 2 diabetes: A real‐world study

Abstract: ObjectiveTo investigate the association between serum unconjugated bilirubin (UCB) within normal limits and chronic kidney disease (CKD) in T2DM patients.MethodThis cross‐sectional, real‐world study was performed in 8661 hospitalised T2DM patients. The subjects were stratified into quintiles based on serum UCB levels. The clinical characteristics and CKD prevalence were compared among the UCB quantile groups. The associations of serum UCB levels and quintiles with CKD were also analysed by binary logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“… 57 Other clinical explorations have found that bilirubin is associated with the renal function, macrovascular or microvascular complications such as urinary albumin excretion. 58–60 Therefore, these findings could support that mildly increased serum bilirubin, especially SBiL could be have a protective consequence on DFU, thus, maintenance of the levels of SBiL or the antioxidant ability maybe a critical target for DFU.…”
Section: Discussionmentioning
confidence: 74%
“… 57 Other clinical explorations have found that bilirubin is associated with the renal function, macrovascular or microvascular complications such as urinary albumin excretion. 58–60 Therefore, these findings could support that mildly increased serum bilirubin, especially SBiL could be have a protective consequence on DFU, thus, maintenance of the levels of SBiL or the antioxidant ability maybe a critical target for DFU.…”
Section: Discussionmentioning
confidence: 74%